2022
DOI: 10.1007/s13760-022-02039-3
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrobasilar artery elongation in migraine—a retrospective cross-sectional study

Abstract: Background Numerous but inconclusive findings have sparked an ongoing debate about whether the arteries of migraine patients undergo vascular alterations. The outlet angle of the superior cerebellar artery (SUCA) and the lateral displacement of basilar arteries are good surrogate parameters for determining elongation of the vertebrobasilar arteries. Methods We retrospectively determined the SUCA outlet angle and the lateral displacement of the basilar arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…69 A longitudinal study by Ngo et al revealed that the bending length of BA after approximately 10 years was more pronounced in patients with VAD than in non-VAD patients. 70 In the present study, we observed that the total lateral displacement of BA increases with aging within the migraine group, which is similar to the result of Hensel et al 29 In addition, we found that the height of BA bifurcation increases with aging in both groups, which is similar to the findings of previous studies. 70,71 Nevertheless, it was observed that despite the control group having a higher average age compared to the migraine group, the height of the BA bifurcation was found to be significantly higher in migraineurs.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…69 A longitudinal study by Ngo et al revealed that the bending length of BA after approximately 10 years was more pronounced in patients with VAD than in non-VAD patients. 70 In the present study, we observed that the total lateral displacement of BA increases with aging within the migraine group, which is similar to the result of Hensel et al 29 In addition, we found that the height of BA bifurcation increases with aging in both groups, which is similar to the findings of previous studies. 70,71 Nevertheless, it was observed that despite the control group having a higher average age compared to the migraine group, the height of the BA bifurcation was found to be significantly higher in migraineurs.…”
Section: Discussionsupporting
confidence: 92%
“…23 Several studies have revealed that patients with migraine, particularly MwA patients without a VAD, exhibit a higher degree of lateral displacement of the BA compared to control subjects. [27][28][29] An MR angiography study conducted by Hensel et al found that lateral displacement of the BA in patients with migraine was higher than that in control subjects, and the frequency of the displacement showed a peak shift to the right. Researchers postulate that lateral displacement could be due to contralateral hypoplasia of the VA. 29 Our study also found the same results as those of Hensel et al, but our results were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations